2022
DOI: 10.1002/brb3.2848
|View full text |Cite
|
Sign up to set email alerts
|

Responses in left inferior frontal gyrus are altered for speech‐in‐noise processing, but not for clear speech in autism

Abstract: People with an autism spectrum disorder (ASD) often have difficulties with recognising what another person is saying in noisy conditions such as in a crowded classroom or a restaurant.The underlying neural mechanisms of this speech perception difficulty are unclear. In typically developed individuals, three cerebral cortex regions are particularly related to speech-in-noise perception: The left inferior frontal gyrus (IFG), the right insula and the left inferior parietal lobule (IPL) (Alain et al., HBM, 2018).… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…It is possible that in the current study, the auditory signal was not, or at least not sufficiently degraded for these effects to emerge. A recent study by Schelinski and Kriegstein (Schelinski & von Kriegstein, 2022) compared 17 ASD and 17 TD controls in an auditory speech recognition task during fMRI acquisition. The investigators found lower BOLD responses in the ASD group in the left IFG (inferior frontal gyrus) for only auditory stimuli that were masked with noise but not for unmasked stimuli, providing support for this interpretation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that in the current study, the auditory signal was not, or at least not sufficiently degraded for these effects to emerge. A recent study by Schelinski and Kriegstein (Schelinski & von Kriegstein, 2022) compared 17 ASD and 17 TD controls in an auditory speech recognition task during fMRI acquisition. The investigators found lower BOLD responses in the ASD group in the left IFG (inferior frontal gyrus) for only auditory stimuli that were masked with noise but not for unmasked stimuli, providing support for this interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…There is a great amount of evidence suggesting that the primary region where MSI is typically observed across a wide range of stimuli and tasks in neurotypicals (e.g., Beauchamp et al, 2004; Bushara et al, 2001; Calvert et al, 2000; van Atteveldt et al, 2010) shows an altered function and anatomy in ASD (Patriquin et al, 2016; see also Stevenson et al, 2016 for a review). Posterior parts of the superior temporal sulcus (STS) have been shown to be structurally altered in ASD (Boddaert et al, 2004; Boddaert et al, 2009; Boddaert & Zilbovicius, 2002; Levitt et al, 2003) and to display different patterns of activation to speech sounds (Jochaut et al, 2015; Redcay & Courchesne, 2008; Schelinski & von Kriegstein, 2022). In addition, there is evidence that visual speech engages visual motion region V5 (MT) differently in ASD (Borowiak et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains unclear how efficiently autistic listeners adapt to novel and varying voices. Autistic adult listeners’ neural processing of word-and-sentence level spoken language appears to be similar to non-autistic adults’, in both clear and noisy environments 56 , 57 . Likewise, processing of social characteristics of voices such as gender or age have been shown to be unaffected in autistic listeners 58 .…”
Section: Introductionmentioning
confidence: 92%
“…Furthermore, in the same study within the autistic group, the P1 amplitudes in quiet and in noise were not significantly different from each other, consistent with other published evidence of less efficient speech sound processing in autistic individuals even under optimal listening conditions. Recent neuroimaging speech-in-noise studies in autistic adolescents and adults also noted subtle differences from the neurotypical comparison groups in the activation of several cortical and subcortical regions involved in speech processing (Hernandez et al 2020; Schelinski et al 2022; Schelinski & von Kriegstein 2023). Those findings suggested reduced efficiency of acoustic feature processing or increased reliance on top-down compensatory processes to increase sensitivity to speech presented in background noise.…”
mentioning
confidence: 99%